Current Research Trends and Prospects for Yield and Quality Improvement in Sesame, an Important Oilseed Crop - Yadav, Rashmi; Kalia, Sanjay; Rangan, Parimalan; Pradheep, K.; Rao, Govind Pratap; Kaur, Vikender; Pandey, Renu; Rai, Vandna; Vasimalla, Celia Chalam; Langyan, Sapna; Sharma, Sanjula; Thangavel, Boopathi; et al. (Frontiers in Plant Science, 2022)
Climate change is causing a shift in agricultural production, which could impact the economic and cultural contexts of oilseed industry, including sesame. Moreover, environmental threats (biotic and abiotic stresses) affect natural sesame production and thus yield (especially oil content). Little research has been undertaken for genetic enhancement and quality improvement of sesame and underlying mechanisms of sesame stress tolerance have not been elucidated. This review reveals the challenges faced by farmers/researchers growing sesame crops and the potential genetic and genomic resources for addressing the threats. Detailed strategies for protecting sesame from environmental threats and improving yield include: (1) developing sesame varieties that tolerate phyllody, root rot disease, and waterlogging, (2) investigating agro-morphological traits that would benefit farmers, such as determinate growth, prostrate habit, and delayed response to seed shattering, (3) using wild relatives of sesame for wide hybridization, and (4) advancing existing strategies to maintain sesame production under changing climatic conditions. Future research programs need to add technologies and develop the best research strategies toward economical and sustainable development.